Does land-based exercise-therapy improve physical activity in people with knee osteoarthritis? A systematic review with meta-analyses. Issue 11 (November 2022) - Bell, E.C.; Wallis, J.A.; Goff, A.J.; Crossley, K.M.; O'Halloran, P.; Barton, C.J.
Summary: Primary objective: Investigate the effects of land-based exercise-therapy on physical activity in people with knee osteoarthritis (KOA). Design: Systematic review and meta-analysis of randomised or quasi-randomised trials investigating land-based exercise-therapy on physical activity, fitness, and general health in people with KOA. We updated a 2013 Cochrane review search on exercise-therapy for KOA in April 2021 and applied the Cochrane Risk-of-Bias Tool 1.0 to included articles. Standardised mean differences (SMDs) and 95% confidence intervals (CI) were calculated. GRADE was used to assess certainty of the evidence. Results: Twenty-eight randomised controlled trials (2, 789 participants) evaluating the effects of resistance-training ( n  = 10), walking ( n  = 6) and mixed-exercise programs ( n  = 7) were identified. Low to moderate certainty evidence indicated small increases in physical activity for exercise-therapy compared to non-exercise interventions in the short-term (SMD, 95% CI = 0.29, 0.09 to 0.50), but not the medium- (0.03,  −0.11 to 0.18) or long-term (−0.06,  −0.34 to 0.22). Low certainty evidence indicated large increases in physical activity for walking programs (0.53, 0.11 to 0.95) and mixed-exercise programs (0.67, 0.37 to 0.97) compared to non-exercise interventions in the short-term. Low certainty evidence indicated moderate and small increases in physical activity for resistance-training combined with education focused on pain coping skills and self-efficacy compared to education alone at medium-term follow-up (0.45, 0.19 to 0.71). Conclusion: Walking and mixed-exercise, but not resistance-training, may improve physical activity in people with KOA in the short-term. Combining resistance-training with education may increase physical activity in the medium-, but not the long-term, highlighting the potential importance of developing more effective longer-term interventions for people with KOA. Future studies evaluating land-based exercise-therapy are encouraged to include physical activity outcomes and longer-term follow-up to increase the certainty of evidence.